Towards Professionalism and Police Legitimacy? An Examination of the Education and Training Reforms of the Police in the Republic of Ireland - Jeremy Thompson; Brian Payne (Education Sciences, 2019)
In this paper, we present a thought piece examining recent core policing reforms introduced in the Republic of Ireland (ROI), responding to a perceived crisis of legitimacy, for An Garda Síochána (AGS) (translated: ‘The Guardian of the Peace’). Central to this process is the critical reform of the education and training of police and their relationship to the professionalisation and legitimacy of policing. In this paper, we put forward an explorative analysis of the potential link between the professional education of police and their perceived legitimacy. A literature review was carried out on the reform process, including the related elements of police education, training, professionalisation, community policing, police legitimacy, code of ethics (CoE) and police culture. We consider the espoused ambition to professionalise policing via processes including the provision of professional learning in universities and how this might be deemed to contribute (or not) to legitimacy. While no empirical research to date has been carried out on these specific reforms in the ROI, the reform recommendations had several resonances with broader examination of the themes and challenges (in particular police ethics and culture) associated with reform of democratic policing in other jurisdictions, particularly with respect to increasing professional learning and perceived police legitimacy.